The Effect Of Purple Sweet Potato Flour Substitution On The Quality Of Serabi - Zulindrawati, Fenny; Syarif, Wirnelis (Universitas Negeri Padang, 2023)
The purpose of this study is to see how the quality of serabi is affected by substituting purple sweet potato flour by as much as 20%, 40%, or 60%. A pure experimental study with a completely randomized design is what this form of research is (CRD). The subject of this study was serabi made using purple sweet potato flour, which improved the quality of the serabis by 20%, 40%, and 60%, respectively. Organoleptic tests were administered to three expert panelists, all of whom are lecturers in the Department of Family Welfare Sciences at Padang State University, to collect data for this study. Purple sweet potato flour served as the study's independent variable. The quality of the serabi created, including its shape, color, scent, texture, and taste, is the dependent variable in this study. The data analysis technique utilized to examine organoleptic test results was Analysis of Variance (ANOVA). The collected data is then tabulated in tabular form and examined using the test for each data set. The data analysis was then carried out, and if the data generated by Fcount was more than Ftable, Duncan's test was used. The findings of this study show that there is a substantial effect on the quality of color and texture (porous) on serabi, but no significant difference in form, scent, texture (soft), or taste. It may be determined that the treatment (X1) with a 20 percent substitution of purple sweet potato flour yielded the greatest results in the quality test of the best purple sweet potato flour serabi.